1985
DOI: 10.1017/s0022215100096389
|View full text |Cite
|
Sign up to set email alerts
|

The radionuclide diagnosis, evaluation, and follow-up of malignant external otitis (MEO)

Abstract: A patient suffering from malignant external otitis (MEO) underwent early blood pool scanning followed after 2 hours by 99m To MDP bone scanning, and serial Ga-67 citrate scintigraphies of the skull. The former two procedures served as a diagnostic tool to MEO. The latter was used for estimating the extent of the infective process, and for following-up the efficacy of treatment.The complementary role of these three procedures in the diagnosis, and follow-up of MEO, with special emphasis on immediate blood pool … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 17 publications
(9 reference statements)
0
9
0
Order By: Relevance
“…Uri et al (1991) reported the usefulness of a gallium scan in establishing the diagnosis. Gallium scanning is useful for monitoring the results of treatment because its uptake reduces as osteomyelitis is controlled with therapy (Garty et al, 1985). Its uptake reduces totally with control of infection as happened in this patient after some months of therapy.…”
Section: Discussionmentioning
confidence: 92%
“…Uri et al (1991) reported the usefulness of a gallium scan in establishing the diagnosis. Gallium scanning is useful for monitoring the results of treatment because its uptake reduces as osteomyelitis is controlled with therapy (Garty et al, 1985). Its uptake reduces totally with control of infection as happened in this patient after some months of therapy.…”
Section: Discussionmentioning
confidence: 92%
“…Since adequately treated infectious lesions lose the ability to concentrate the tracer. Therefore, these traces are often used in treatment response monitoring [ 26 ]. Disadvantages are the high costs, time consumption, and high radiation dose [ 25 , 27 ].…”
Section: Nuclear Imagingmentioning
confidence: 99%
“…Also in conventional nuclear imaging many of the diagnostically valuable changes stay present after the resolution of disease. As stated above, Technetium-99 m is indicative of osteoblastic activity in damaged bone [ 9 •, 26 ]. Because of prolonged activities of osteoblasts in previously affected bone, Tc-99 m will continue to demonstrate previously affected areas as hot spots for many years [ 24 , 33 ].…”
Section: Imaging Modalities For Sbo—follow-upmentioning
confidence: 99%
“…Interestingly, in this case, radiology did not at any stage suggest bony erosion around the jugular foramen, only mastoiditis. Garty et al (1985) point out the deficiency of plain radiology and polytomograms of the skull base in the diagnosis of Pseudomonas osteomyelitis, as there may be no bony erosion initially and 30 to 50 per cent demineralisation is necessary in cancellous bone before a…”
Section: Casementioning
confidence: 95%